A program centered on smart electrically assisted bicycle outings for rehabilitation after breast cancer: A pilot study. (February 2022) - Rey-Barth, Sophie; Pinsault, Nicolas; Terrisse, Hugo; Eychenne, Claire; Rolland, Carole; Foote, Alison; Guyot, Catherine; Bosson, Jean-Luc
Highlights: Outings on electrically assisted bicycles are feasible, supervised or in autonomy. Patients appreciated and adhered to the education and electric bike program. Personalized assistance allowed everyone to improve their physical condition. Joint pursuits promote long-term physical activity. Abstract: The benefits of physical activity during cancer care and rehabilitation are well established, however introducing and maintaining healthy behaviors in the long-term remains challenging. Technological advances in electrically assisted bicycles and on-board sensors led us to propose an original rehabilitation program combining smart electric bicycle outings with health education. This was a pilot study with physical activity questionnaires and endurance tests to evaluate physical activity following a 6-week program comprising 2 bicycle outings per week in groups of 5 (supervised or not) with briefing and debriefing supplemented by health education sessions. Fourteen post-breast cancer patients participated (median age 52 [IQR 46–55]). A gain of at least 2 International Physical Activity Questionnaire points and over 600 MET.min/week was achieved by 9/10 (90%; 95%CI[55.5–99.7]) women. The feasibility of the program was clearly demonstrated, with excellent patient adherence (11/12 planned 2 h outings per patient). The electric bicycle program strengthened the womens' physiological capacities through personalized levels of electrical assistance made possible by the fine settings of the motorization. This enabled the whole group to achieve the outing objectives together despite very variable levels of deconditioning. The pleasure shared in the group activity and personal empowerment gained should promote long-term maintenance of physical activity.